USMCA 2.0: a few improvements but far from a 'healthy' trade treaty - Ronald Labonté; Deborah Gleeson; Courtney L. McNamara (BMC, 2020)
Abstract The USMCA (NAFTA 2.0), although signed over a year ago, went through several months of renegotiation of certain of its new rules that the Democrat-controlled US Congress wanted altered or strengthened. In December a 'Protocol of Amendment' was agreed upon and signed by the three Parties (the USA, Mexico, and Canada). A number of tough, new measures governing pharmaceuticals were revised or deleted, making it potentially easier for generic competition and lower drug costs in all three countries. Rules on protection of labour rights were also strengthened, lowering the threshold at which a complaint of unfair labour practices could be initiated. Procedures for investigating such a complaint or resolving a formal dispute were also improved. Similar procedural improvements were made on measures affecting environmental protection. These Protocol agreements are more health-positive than health-negative, and in the case of pharmaceuticals are of significant impact. Overall, however, these amendments are simply a political fine-tuning of the agreement. Concerns raised in our earlier health impact assessment of the USMCA, notably how the agreement's regulatory reforms reduce public health policy flexibilities, remain. The agreement continues to subordinate known or potential health costs of many of its measures to dubious claims of aggregate economic gains. Moreover, these gains, if materialized, are likely to accrue to those atop the income/wealth hierarchies in all three nations.